Pengembangan Media Pembelajaran Video Interaktif Berbasis Canva pada Materi Hobi Siswa Kelas VIII MTs Olang Luwu - Ahmad, Nurmiati; Mustafa; Yamin, Muh.; Sudarmin, Nurfaisan; Kanukung, Nova Anugrah; Wahyuni, Iin; Fatimah (Jurusan Pendidikan Bahasa Arab, 2025)
This study aims to develop an interactive video-based learning media using Canva for the topic of hobbies for Grade VIII students at MTs Olang Luwu. The research employs a Research and Development (R&D) method using the ADDIE model, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The study was conducted on Grade VIII students at MTs Olang Luwu, involving 15 respondents in February 2025. Data collection techniques in this study included observation, interviews, questionnaires, and documentation. The research results showed that the media validator gave a score of 91%, categorized as very valid, and the material validator gave a score of 95%, also categorized as very valid. The practicality test by the subject teacher resulted in 88%, categorized as very practical, and the practicality test by students using response questionnaires yielded 78%, categorized as practical. The conclusion of this study is that the Canva-based interactive video learning media is highly valid and practical to be used as a learning tool for Arabic language lessons on the topic of hobbies, and it effectively enhances students' motivation and engagement in the learning process.